The effect of aromatic ring size in electron deficient semiconducting polymers for n-type organic thermoelectrics. Issue 43 (13th August 2020) - Alsufyani, Maryam; Hallani, Rawad K.; Wang, Suhao; Xiao, Mingfei; Ji, Xudong; Paulsen, Bryan D.; Xu, Kai; Bristow, Helen; Chen, Hu; Chen, Xingxing; Sirringhaus, Henning; Rivnay, Jonathan; et al.
Abstract : N-type semiconducting polymers have been recently utilized in thermoelectric devices, however they have typically exhibited low electrical conductivities and poor device stability, in contrast to p-type semiconductors, which have been much higher performing. Abstract : N-type semiconducting polymers have been recently utilized in thermoelectric devices, however they have typically exhibited low electrical conductivities and poor device stability, in contrast to p-type semiconductors, which have been much higher performing. This is due in particular to the n-type semiconductor's low doping efficiency, and poor charge carrier mobility. Strategies to enhance the thermoelectric performance of n-type materials include optimizing the electron affinity (EA) with respect to the dopant to improve the doping process and increasing the charge carrier mobility through enhanced molecular packing. Here, we report the design, synthesis and characterization of fused electron-deficient n-type copolymers incorporating the electron withdrawing lactone unit along the backbone. The polymers were synthesized using metal-free aldol condensation conditions to explore the effect of enlarging the central phenyl ring to a naphthalene ring, on the electrical conductivity. When n-doped with N-DMBI, electrical conductivities of up to 0.28 S cm −1, Seebeck coefficients of −75 μV K −1 and maximum Power factors of 0.16 μW m −1 K −2 were observed from the polymer with the largest electron affinity of −4.68 eV. Extending the aromatic ring reduced the electron affinity, due to reducing the density of electron withdrawing groups and subsequently the electrical conductivity reduced by almost two orders of magnitude.